Reframing Spatial Hazard Education with Interactive Digital Media and Regionalized Content in Secondary Schools - Faridh Arganatha Diwangkara; Purwanto; ivy, Tan Geok Chin (Future Space: Studies in Geo-Education, 2025)
Modern geography education necessitates technology-integrated materials to visualize complex spatial phenomena effectively. Addressing this need, this study employs the ADDIE model to develop "IC-Learn," an E-Module based on the I-Care learning framework, designed to enhance students' understanding of localized landslide disasters. The research objectives are twofold: 1) to develop the IC-Learn E-Module using Articulate Storyline, and 2) to evaluate its feasibility and effectiveness in improving students' cognitive learning outcomes. The module was tested on Year XII students using a One-Group Pretest-Posttest design. Validity tests by material and media experts confirmed the product’s high feasibility. Statistical analysis using the Paired Sample T-Test yielded a significance value of <0.05, confirming that the intervention significantly impacted student knowledge. Furthermore, the effectiveness test resulted in an N-Gain score of 0.48 (Medium category). In the context of this research, this value implies that while the IC-Learn module effectively bridges the gap between prior knowledge and new cognitive understanding, it is most potent when utilized as a complementary pedagogical tool rather than a standalone instructional method. Consequently, the study concludes that while the I-Care based E-Module is a valid and effective instrument for disaster mitigation education, its optimal implementation requires a blended learning approach where digital interaction is reinforced by teacher scaffolding